The Embodiment of Power in the African (Acoli) and Western Cultural Perspectives as Presented in Okot p’Bitek’s Song of Lawino and Song of Ocol - Ogaro , Gladys Nyaiburi; Munyao, Diana Mutono (African Journal of Education,Science and Technology (AJEST), 2015)
This paper aims to explore the embodiment of power in Africa – in this case Uganda‘s Acoli – and Western cultural perspectives as presented in Okot p‘Bitek‘s Song of Lawino and Song of Ocol. It specifically examines how Okot uses the characters: Lawino, Ocol and Tina as bodies which possess power and how they play out such powers. These bodies are defined by contradictions that illustrate the fact that cultures have their strengths and weaknesses. Ocol and Tina represent Western culture while Lawino‘s body represents African culture. The play of cultural power as emitted through the bodies and speeches of these characters is examined. In this paper, the author argues that Okot p‘Bitek in song of Lawino and song of Ocol plays out the cultural conflicts by Western and Acoli value cultural systems. Both cultural value systems are mechanized in the bodies of characters: Lawino, Ocol, Clementine and also in space which manifests itself as either social or geographical body. Both cultural value systems are presented as complex processes which can either be positive or negative. In Song of Lawino, for instance, Okot presents Ocol, a body upon which power has been invested by the Western culture to out rightly denounce the power of the Acoli culture. Ironically, the power relationship between Ocol and the Western culture present Ocol as a puppet body symbolic in the execution of power. In a cunning way, the Western culture manipulates a way of exercising power over the Acoli culture. This then renders the Western culture ‗invisible‘ while Ocol takes blame. The power of the Western culture seem to liberate and empower on the surface, for example, Ocol and Tina in Song of Lawino, on face value look better in their new outfit of the Western culture but underneath this is enslavement. In Song of Ocol, Ocol is a sophisticated, self-serving and unrepentant character who has embraced the new culture fervently just like Tina in Song of Lawino. The two become submissive to the Western culture as opposed to themselves and their Acoli culture. Ocol‘s adoration of the Western culture and Tina‘s change of behaviour and appearance to suit the West clearly displays how the Western culture has manipulated its ways of power over bodies to regulate and manage them. Ocol sees nothing worth presenting in the old ways and has hardly any reservations in saying so. He asserts that the future is with the western culture and technologies that make it dominant